(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This randomized controlled trial investigated the effects of a 12-week psychomotor training program on object control skills among 20 school girls aged 6 to 7 years from Tiruchendur Taluk, Tamil Nadu. Participants were randomly assigned to an intervention group (n=10) or a control group (n=10). The intervention group underwent three weekly sessions focusing on throwing and bouncing skills, while the control group received no intervention. Object control skills were assessed using the MABAK-2 tool before and after the intervention period. Paired sample t-tests and analysis of covariance (ANCOVA) were used for data analysis. Results showed significant improvements in throwing and bouncing skills within the intervention group, supported by both statistical tests. ANCOVA further demonstrated that post-intervention scores were significantly higher in the intervention group compared to the control group. These findings underscore the efficacy of structured psychomotor training programs in enhancing object control skills among young children.